Pengetahuan Mahasiswa Universitas Muhammadiyah Bandung terkait Konsumsi Pangan Sehat dan Halal Selama Pandemi Covid-19 - Listyaningrum, Ratna Sari; Hidayatuloh, Iip Syarip (Agritechnology, 2023)
Covid-19 is an infectious disease caused by coronavirus. Actions that can be taken are to follow the recommendations of the World Health Organization and the government to protect yourself against infection. Covid-19 causes fever, so the body needs additional energy and nutrition through good nutritional intake to strengthen the immune system. Students are included in generation Z teenagers whose cognition and psychology have developed, so they have great potential to be involved in handling the Covid-19 pandemic. Therefore, research is needed to see and evaluate whether the pandemic has changed the awareness and behavior of healthy food consumption of UMBandung students. The sampling method used is Probability Sampling. The sampling technique used was proportional stratified random sampling. This data collection uses a questionnaire with Google Form. The questionnaire has met the requirements for validity and reliability. The results show that there are differences in awareness and behavior in consuming healthy and halal food by UMBandung students during the Covid-19 pandemic. The changes in question tend to be improvements